Study of the IEC 61850 protocol on multiagent systems for power system applications - Leite, Jônatas Boás [UNESP]; Mantovani, José Roberto Sanches [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
Multiagent system (MAS) applications on power systems are justified by their inherent properties of flexible autonomy, reactivity, pro-activeness, social ability and the distributed nature of agents. The design methodology of MAS applications has different stages, of which the choice of the agent communication protocol is essential. Therefore, in this paper, the adoption of the IEC 61850 standard as agent communication protocol is investigated using a set of basic requirements like network scheme, information format and agency coordination. The performed study reveals the potentialities of the IEC 61850 protocol once there is not a specification of the communication among agents.
Keywords: Communication Protocol; IEC 61850 standard; Multiagent System; Power Systems